STUDIES ON A LIPOPROTEINASE OF GROUP A STREPTOCOCCI - Krumwiede, Elma (The Rockefeller University Press, 1954)
The opalescence produced in serum by group A streptococci has been investigated. The development of opalescence is shown to be initiated by an enzyme attached to the bacterial cell which acts upon the α(1)-lipoprotein fraction of serum liberating the lipids from the protein. This enzyme has been termed a lipoproteinase. Evidence is presented which suggests that the degree of opalescence which develops following lipoproteinase activity is influenced not only by factors attached to the bacterial cell but also by substances present in serum. The lipoproteinase is antigenic and many human sera contain specific antibodies which inhibit the action of the enzyme.